Anatomy of the pecten and its functional correlation in domestic fowl - Venkatesan, S; Ramesh, Geetha (The Indian Journal of Animal Sciences, 2011)
The studyon the gross morphology, morphogenesis, histomorphology and histochemistryofthe pecten in the domestic fowl (Gallus domesticus) was conducted in 60 fertile eggs and 108 post hatch birds. The pecten is atrapezoidal, black velvety mass in the ventral part ofthe fundus rising from the elongated optic disc. In the chick embryos, the primordium of the pecten was noticed on the fourth day. The development ofthe pecten was divided into 4 phases, viz. formation of primordial pecten, formation of plate like pecten, pleat formation with pigmentation and bridge formation with high. vascularisation. Histologically, the pecten consisted ofa bridge, avascular network ofboth large and small blood vessels and pigmented intervascular tissue, which lacked muscular and nervous tissue. The richness of the capillaries, close association ofthe pecten with vitreous body, pleated arrangement to increase the surface area, its proximity to the retina and avascularityofthe retina appeared to confirm its nutritive function. The other functions such as erectile organ, metabolie function and phagocytic function of the peripectinate cells were discussed. The functions such as intraocluar shade and magnetic sensor lacked apparent anatomical basis. Histochemically, the pecten was positive for PAS and acid phosphatase activity. The presence ofmelanin granules suggested that the pecten had a light absorbing function Â